The Nexus Between Working Capital Management and Firm Performance: Leverage as a Moderator - Romsiya, R.; Tharshiga, P.; Rathiranee, Y. (Faculty of Business Studies University of Vavuniya Sri Lanka, 2024)
This study seeks to investigate the impact of WCM on firm performance and the moderating role of leverage in this relationship. Employing a quantitative approach, the study analyzes secondary data from the annual reports of forty-two companies spanning the periods from 2018/19 to 2022/23. The methodology includes descriptive statistics, correlation analysis, unit root tests, and panel regression models to ensure a robust econometric evaluation. The findings indicate that higher liquidity, as reflected by the Current Ratio (CR), positively influences both ROA and ROE, while an efficient DSO significantly improves asset efficiency. Additionally, the research reveals that leverage moderates the relationship between DSO and ROA, suggesting that firms with elevated debt levels must prioritize rapid collection of receivables to mitigate liquidity risks. Conversely, DIO and DPO demonstrate a limited direct effect on firm performance within this sector. These results underscore the importance of tailored WCM strategies and offer valuable insights for policymakers aiming to develop supportive frameworks. Future research should consider broader samples, explore additional moderating variables, and incorporate qualitative methods to deepen the understanding of WCM dynamics in various contexts. This work contributes to both academic and professional literature by highlighting the essential role of effective WCM in enhancing firm performance, particularly in high-leverage environments.
Keywords: Working capital management; ROA,ROE Firm performance and Leverage